The Question of the Return of Jews to Poland in the National Camp Press in the Years 1930-1939 - Głębocki, Bohdan (Sensus Historiae, 2025)
The article presents a review of publications concerning the return of Jews from abroad to Poland, as featured in the national camp press between 1930 and 1939. It examines the then-current usage of the term “remigration,” which was typically limited to ethnic Poles, as well as alternative expressions applied in reference to Jews. The article analyzes the use of a propagandistically charged and repeatedly circulated - but factually false - accusation against Minister of the Interior, Felicjan Sławoj-Składkowski, related to the legal status regulation of Jews originating from the former Russian Empire in 1928. It also identifies connections between these publications and international developments. Special attention is given to the national press’s reception of the 1938 expulsion of Polish Jewish citizens from the Third Reich as part of the Polenaktion, and to the far-reaching consequences of this event.